Advanced landscapes in public space: Spontaneous, wild, unexpected. New paradigms for open spaces of European cities - Dessì, Adriano (EAAE Annual Conference Proceedings, 2025)
Landscape is a concept that increasingly experiences advancement in public space design. But we also know that the most important public spaces in Europe - such as Piazza del Campo in Siena, Potsdamer Platz in Berlin, the Buttes-Chaumont Park in Paris, and so on - had historically already been pieces of a pre-existing landscape that has been incorporated by the city. The basic relationship between nature and urban open space – ecological, morphological, and social, at the same time - is a quality of European public space that has been progressively lost. Yet, in fact, in the European city the possibility exists to find its ancient – and never forgotten – relation with the natural dimension. It is precisely defined by the deep comprehension of its system of public and private open spaces, in their typological and morphological structure, and ultimately down to their material features. The paper briefly retraces this relationship and proposes certain contemporary cases in which the MUST connecting the public spaces to the original landscape could be interpreted as a new way of imagining and designing the European city. Is its consequence the LESS of human presence, materials, and architecture?